The Influence of Basic Literacy on the Interest and Reading Ability of Elementary School Students in Rangsang District - Salbiah; Masrul; Imam Hanafi (Institute of Educational, Research, and Community Service, 2024)
This research aims to determine the influence of basic literacy on the reading interest and ability of elementary school students in Rangsang District. The research method used was an experiment with a pretest-posttest control group design. The research sample consisted of fourth-grade students from SD Negeri 19 Repan and SDN 18 Penyagun, Rangsang District. The instruments used in this research were a reading interest questionnaire and a reading ability test. The data obtained were analyzed using simple linear regression tests. The results of the study indicated that basic literacy had a significant influence on students' reading interest and ability. The correlation coefficients of 0,414 for reading interest and 0,390 for reading ability showed a fairly strong relationship between basic literacy and student learning outcomes. The R Square values of 0,171 and 0,152 respectively indicated that about 17.1% and 15.2% of the variation in reading interest and ability could be explained by basic literacy. This study provides strong empirical evidence of the effectiveness of basic literacy in enhancing the reading interest and ability of elementary school students in Rangsang District. These findings have important implications for educational policy and practice, particularly in regions facing literacy challenges. Integrating intensive and systematic basic literacy programs into the elementary school curriculum can be an effective strategy to improve students' literacy skills, which in turn will support their overall academic success.